CORRELATION BETWEEN PREEXPONENTIAL FACTOR AND ACTIVATION ENERGY OF ISOAMYLALCOHOL HYDROGENOLYSIS ON PLATINUM CATALYSTS - Triyono Triyono (Indonesian Journal of Chemistry, 2004)
Arrhenius equation stated that reaction will proceed faster at higher temperature and with lower activation energy (Ea). Many literatures reported that preexponential factor (A) is constant for certain reaction and there is no relation between A and Ea. Experiment on the reaction of isoamylalcohol hydrogenolysis showed that logarithm of A increased linearly with Ea. The result of this investigation suggests that the rate of a process is affected by the number of active centers on the surface of a catalysts, which influences the value of the pre-exponential term in the expression for the rate constant of a reaction. An increase in the number of active centers corresponds to a higher value of A, the active centers would be less effective and is attended by a growth in the value of Ea. Therefore, reaction with lower activation energy will not always has higher reaction rate due to decreasing of Ea.